Ambiguity aversion among student subjects: the role of probability interval and emotional parameters. Issue 4 (3rd March 2016) - Yesuf, Mahmud; Feinberg, Robert M.
Abstract: In the literature on decision-making under uncertainty, it has been shown that decision-makers tend to prefer taking gambles with known-risk probabilities (pure risk) over equivalent gambles with ambiguous probabilities. This article contributes to the ongoing discussion in the literature on cognitive and non-cognitive covariates of ambiguity aversion. Through a series of experiments, it finds that subjects are more ambiguity-averse to prospects with wide probability intervals than to an equivalent prospect with narrow intervals, and that subjects' inherent trust, happiness and level of optimism affect the level of ambiguity aversion.